1997
DOI: 10.1002/aic.690430513
|View full text |Cite
|
Sign up to set email alerts
|

Detecting persistent gross errors by sequential analysis of principal components

Abstract: Measurements such as flow rates from a chemical process violate conservation laws and other process constraints because they are contaminated by random errors and possibly gross errors such as process disturbances, leaks, departures from steady state, and biased instrumentation. Data reconcilation is aimed at estimating the true values of measured variables that are consistent with the constraints, at detecting gross errors, and at solving for unmeasured variables. An approach to constructing sequential princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Narasimhan and Mah (1987) and Crowe (1988) showed that these two are equivalent and have maximum power for the case of one gross error. Later, principal‐component tests (PCT) were proposed by Tong and Crowe (1995,1996) as an alternative for multiple bias and leak identification. Industrial applications of PCMT were reported by Tong and Bluck (1998), who indicated that tests based on principal‐component analysis (PCA) are more sensitive to subtle gross errors than others, and have greater power to correctly identify the variables in error than the conventional nodal, measurement, and global tests.…”
Section: Induced Biasmentioning
confidence: 99%
“…Narasimhan and Mah (1987) and Crowe (1988) showed that these two are equivalent and have maximum power for the case of one gross error. Later, principal‐component tests (PCT) were proposed by Tong and Crowe (1995,1996) as an alternative for multiple bias and leak identification. Industrial applications of PCMT were reported by Tong and Bluck (1998), who indicated that tests based on principal‐component analysis (PCA) are more sensitive to subtle gross errors than others, and have greater power to correctly identify the variables in error than the conventional nodal, measurement, and global tests.…”
Section: Induced Biasmentioning
confidence: 99%
“…This task is termed dynamic data rectification (or dynamic data reconciliation) (Darouach & Zasadzinski, 1991;Liebman, Edgar & Lasdon, 1992;Singhal & Seborg, 2000), and differs to the "steady" rectification techniques reported in the literature (Morad, Young & Svrcek, 2005;Tong & Crowe, 1997) which are designed around the steady state operation of processes and thus do not need to take into account the process dynamics. Dynamic data rectification is especially challenging when the state and/or measurement functions are highly non-linear, and the posterior distribution of the process states, is not Gaussian.…”
Section: Introductionmentioning
confidence: 99%
“…The key process variables are normally used for closed-loop control, whereas the great majority of measured variables remain unused or merely serve for monitoring the states of the process. A lot of research is now being conducted to find ways to make better use of this wealth of information that characterizes the real behavior of the process: development of softsensors (Aynsley et al, 1993), fault diagnosis (Dunia et al, 1996;Hoskins et al, 1991;MacGregor, 1995;Tong and Crowe, 1996;Wise and Ricker, 1991), statistical process monitoring (Chen et al, 1996;Nomikos et al, 1994;Piovoso and Kosanovich, 19941, and data reconciliation (Crowe et al, 1983;Crowe, 1986Crowe, ,1996Hodouin and Everell, 1980;Karjala and Himmelblau, 1994;Liebman et al, 1992;Mah, 1990;Romagnoli and Stephanopoulos, 1981;Schraa and Crowe, 1996;Smith and Ichiyen, 1973). The latter topic is the subject of this article.…”
Section: Introductionmentioning
confidence: 99%
“…Nonrandom measurement errors, such as persistent gross errors, must first be detected and then removed or corrected. Indeed, meaningful data adjustments can be achieved if and only if there is no gross error present in the data (Tong and Crowe, 1996). Gross-error detection has been the subject of a significant amount of research (Mah, 1990;Rollins and Davis, 1992;Tjoa and Biegler, 1991;Tong and Crowe, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation